Numerical assessment of a soil moisture controlled wastewater SDI disposal system in Alabama Black Belt Prairie. (January 2021) - He, Jiajie; Dougherty, Mark; Chen, Zhongbing
Abstract: To promote the environmental sustainability of rural sanitation, a soil moisture controlled wastewater subsurface drip irrigation (SDI) dispersal system was field tested in the Black Belt Prairie of Alabama, USA. The soil moisture control strategy was designed to regulate wastewater disposal timing according to drain field conditions to prevent hydraulic overloading and corresponding environmental hazard. CW2D/HYDRUS simulation modeling was utilized to explore difficult-to-measure aspects of system performance. While the control system successfully adapted hydraulic loading rate to changing drain field conditions, saturated field conditions during the dormant season presented practical application challenges. The paired field experiment and simulation model demonstrate that soil biofilm growth was stimulated in the vicinity of drip emitters. Although biofilm growth is critical in maintaining adequate COD and N H 4 + − N removal efficiencies, the efficient removal of biodegradable COD itself by soil biofilm limits denitrification of formed N O 3 − − N . Furthermore, stimulated soil biofilm growth can create soil clogging around drip emitters, which was discerned in the field experiment along with salt accumulation, both of which were verified by simulation. Comparable modeling of system performance in sand and clay media demonstrate that the placement of soil moisture sensors within the drain field can have pronounced impacts on system hydraulic performance, depending on the soil permeability. Overall, the soil moisture control strategy tested is shown as a viable supplemental technology to promote the environmental sustainability of rural sanitation systems. Highlights: The system prevents hydraulic dosing during unfavorable drain field conditions. Bacterial growth around the drip emitters is crucial for wastewater treatment. Organic carbon and heterotrophs profiles mismatch the demand of denitrification. System performance is sensitive to soil permeability and feedback sensor position.